PENGARUH PENGGUNAAN KEY RELATION CHART (KR-CHART) DALAM MODEL PEMBELAJARAN GUIDED DESCOVERY TERHADAP PENCAPAIAN KOMPETENSI IPA PESERTA DIDIK KELAS VIII DI SMP N 3 PADANG - Eka Susanti; Yurnetti Yurnetti; Ermaniati Ramli (PILLAR OF PHYSICS EDUCATION, 2015)
Various ways can be done to improve the competence of learner that includes the competent of knowledge, skills and attitude. One of the ways is to design learning appropriate ti the needs of students. In terms of instructional materials or learning models. Using KR-Chart in guided discovery learning model is one of the altenative to increase the competence. This research aims to look at the effect of using KR-Chart in guide discovery learning model to the achievement of student competencies at the SMP 3 Padang. This research classified into Quasi Experimen research with design Randomized Control Group Only Design. The research population was all students in grade VIII registered in the academic year 2013/2014. Sampling was carry out by using purposive sampling. Research data includes knowledge competencies, skills and attitude. The research instrument is in the form of a written test for competency knowledge, scorring rubric for competency skills and observation sheet for competence of attitude. Data were analyzed using statistical test of equality of two average (t-test). The result of the research shows averange result of experimental class learning higher than the control for the third competency. Throght testing the equality of two averange turn differences competence of learners experimental class and control class differend significantly on the real level of significant 0,05. This difference is believed to be the effect of the treatment given to the experimental class, so that it can be said that hypothesis is accepted